Sialic acid storage diseases. A multiple lysosomal transport defect for acidic monosaccharides. - Mancini, G M (1991)
A defective efflux of free sialic acid from the lysosomal compartment has been found in the clinically heterogeneous group of sialic acid storage disorders. Using radiolabeled sialic acid (NeuAc) as a substrate, we have recently detected and characterized a proton-driven carrier for sialic acid in the lysosomal membrane from rat liver. This carrier also recognizes and transports other acidic monosaccharides, among which are uronic acids. If no alternative routes of glucuronic acid transport exist, the disposal of uronic acids can be affected in the sialic acid storage disorders. In this study we excluded the existence of more than one acidic monosaccharide carrier by measuring uptake kinetics of labeled glucuronic acid [( 3H]GlcAc) in rat lysosomal membrane vesicles. [3H]GlcAc uptake was carrier-mediated with an affinity constant of transport (Kt) of 0.3 mM and the transport could be cis-inhibited or trans-stimulated to the same extent by sialic acid or glucuronic acid. Human lysosomal membrane vesicles isolated from cultured fibroblasts showed the existence of a similar proton-driven transporter with the same properties as the rat liver system (Kt of [3H]GlcAc uptake 0.28 mM). Uptake studies with [3H]NeuAc and [3H]GlcAc in resealed lysosome membrane vesicles from cultured fibroblasts of patients with different clinical presentation of sialic acid storage showed defective carrier-mediated transport for both sugars. Further evidence that the defective transport of acidic sugars represents the primary genetic defect in sialic acid storage diseases was provided by the observation of reduced, half-normal transport rates in lymphoblast-derived lysosomal membrane vesicles from five unrelated obligate heterozygotes. This study reports the first observation of a human lysosomal transport defect for multiple physiological compounds.